STUDI LIVING QUR’AN DALAM ANIMASI UPIN DAN IPIN: REPRESENTASI NASIHAT LUQMAN AL-HAKIM DEPISODE INDAHNYA RUMAH RASA SAYANG - Yahya, Yuangga Kurnia; Mahmudah, Umi (UIN Sunan Kalijaga Yogyakarta, 2024)
This research focuses on the representation of Luqman Hakim's advice in the animation Upin and Ipin episode